(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2014)
The present study evaluates the effect of mirazid (mz) cd95 and cell cycle in rats of gentamicin (gm) induced renal damage for the detection of apoptosis. Albino male rats (rattus norvegicus), weighing 40–50 g were divided into 6 groups; normal saline, orally treated mirazid 10 mg/kg, gm i.p) for 10 days, mz at 2.5, 5, and 10 mg/kg, per oral for 10 days with the same concentration of gm, mz administered concurrently with gm for 10 days. Gm treatment caused nephrotoxicity as evidenced by marked elevation in serum creatinine and urea (152.3 ± 8.6 mg/dl, 1.6 ± 0.12 mg/dl resp) when compared to the saline treated group. Gm cause significant increase in both sub g1 (apoptosis) and cd95, marker of apoptosis, when compared to saline control whereas mz give significant decrease in cd95 (fas and fas ligand detection) and sub g1 (apoptosis).